Economic challenges of oncological diseases' pharmacotherapy - E. A. Ushkalova; S. K. Zyryanov; I. A. Gopienko (IRBIS LLC, 2020)
Oncological diseases rank high in the structure of population morbidity and mortality. They entail considerable direct and indirect economic costs. In the past decades, the cost of oncotherapy has increased significantly, which is largely conditioned by high prices of antitumor drugs, which on average increased by ten times in the past ten years. At the same time, many innovative medications have only minor advantages over cheaper old medications because they are registered based on the data on the achievement of the surrogate endpoint - extension of progression-free survival. The high cost of oncotherapy is associated with financial toxicity that affects negatively the patients' quality of life, their adherence to treatment and consequently survival. To reduce the cost of oncotherapy, it is necessary to conduct pharma-economic analysis, the results of which can serve as the basis to negotiate price-cutting with the manufacturers, as well as to use high-quality generics and biosimilars as effective and safe as their originals, and to monitor effectiveness and safety of all antitumor drugs within the pharmacovigilance framework.